3x - 42 = 3.2 mũ 3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3\(x\) - 42 = 3.23
3\(x\) - 42 = 3.8
3\(x\) - 42 = 24
3\(x\) = 24 + 42
3\(x\) = 66
\(x\) = 66: 3
\(x\) = 22
3x - 42 = 3 . 23
3x - 42 = 3 . 8
3x - 42 = 24
3x = 24 + 42
3x = 66
x = 66 : 3
=> x = 22.
a)3x - 105 : 21 = 19
3x - 5 = 19
3x = 19 + 5
3x = 24
x = 24 : 8
x = 3
b, x - 7 = 14 - 3 . 23
x - 7 = 14 - 3 . 8
x - 7 = 14 - 24
x - 7 = -10
x = (-10) + 7
x = -3
HT và $$$
Bài 2:
a) 3x - 105 : 21= 19 b) x - 7= 14 - 3 . 2^3
3x - 5 = 19 x - 7= 14 - 3.8
3x = 19+ 5 x - 7= 14 - 24
3x = 24 x - 7= -10
x = 24 : 3 x = -10+7
x = 8 x = -3
b) (5/2-3x)=25/9
3x = 5/2-25/9
3x =-5/18
x =-5/18:3
x=-5/54
\(e.\left(x-1\right)^5=-32\)
\(\left(x-1\right)^5=\left(-2\right)^5\)
\(x-1=-2\)
\(x\) \(=-2+1\)
\(x\) \(=-1\)
Vậy \(x=-1\)
a) \(\left(x+3\right)^2-\left(x-4\right)\left(x+8\right)=1\)
\(\Leftrightarrow\left(x^2+6x+9\right)-\left(x^2+4x-32\right)-1=0\)
\(\Leftrightarrow2x=-40\)
\(\Rightarrow x=-20\)
b) \(\left(x+3\right)\left(x^2-3x+9\right)-x\left(x-2\right)\left(x+2\right)=15\)
\(\Leftrightarrow x^3+27-x^3+4x=15\)
\(\Leftrightarrow4x=-12\)
\(\Rightarrow x=-3\)
c) \(\left(x-2\right)^2-\left(x+3\right)^2-4\left(x+1\right)=5\)
\(\Leftrightarrow\left(x^2-4x+4\right)-\left(x^2+6x+9\right)-\left(4x+4\right)=5\)
\(\Leftrightarrow-14x=14\)
\(\Rightarrow x=-1\)
d) \(\left(2x-3\right)\left(2x+3\right)-\left(x-1\right)^2-3x\left(x-5\right)=-44\)
\(\Leftrightarrow4x^2-9-\left(x^2-2x+1\right)-\left(3x^2-15x\right)=-44\)
\(\Leftrightarrow17x=-34\)
\(\Rightarrow x=-2\)
e) \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=49\)
\(\Leftrightarrow x^3-6x^2+12x-8-x^3+27+6x^2+12x+6=49\)
\(\Leftrightarrow24x=24\)
\(\Rightarrow x=1\)
36 . 46 = (3.4)6 = 126
82 . 23 . 162 = (23)2 . 23 . (24)
= 26 . 23 . 24 = 26 + 3 + 4 = 213
23 . 22 . 83 = 23 . 22 . (23)3
= 23 . 22 . 29 = 23 + 2 + 9 = 214
y. y7 = y1 + 7 = y8
\(3^6\cdot4^6=\left(3\cdot4\right)^6=12^6\)
\(8^2\cdot2^3\cdot16^2=\left(2^3\right)^2\cdot2^3\cdot\left(2^4\right)^2\)
\(=2^6\cdot2^3\cdot2^8=2^{17}\)
\(2^3\cdot2^2\cdot8^3=2^5\cdot\left(2^3\right)^3\)
\(2^5\cdot2^9=2^{14}\)
\(y\cdot y^7=y^{1+7}=y^8\)